The Effect of Using Especial Exercises Suggested for Developing of Accuracy Direction by Fencing in Foil for the Players of the National Team of the Young who Handicap - Fadhel, Abdul Kareem; Mohammad, Alaa (Journal of Physical Education, 2010)
In The Handicaps of fencing are considered an important in the society nowadays so the society should contain and help them on passing forward in their challenge for their handicap by preparation of all necessities and different activities within sport.Hence fencing on wheelchairs is on of these activities . The problem of research that was the trainers how to depend on familiar style in training and not giving special abilities in activities in the game the great important , and they depend only on the exercises of competitions , which causes nun – oscillation on the level of the players an not achieving the goal .The researchist has done special exercises in fencing to develop accuracy of direction and practiced on a sample of the players of the National Team for the young who challenge handicap , if it was chosen ( 8 ) players who where divided in two groups by chance : experimental and controlling in quantity of ( 4 ) players : ( 2 ) players from classification ( A ) , and ( 2 ) players from classification ( B ).After finishing the training program that was suggested and doing the test that comes later , the researchist used ( T ) test for connected samples for the correction of meaningful differences inside the group , and using ( T ) test for free samples for the calculation of meaningful differences in the test that comes later for the two groups : experimental and controlling , and after getting the value ( T ) that was calculated and comparing it in its table value , the results were founded meaningful differences for the two groups in the second test and first test and founded meaningful differences in the second test for the experimental group , because of display of this group to the special exercises. Therefore, the researchist included many conclusion and recommendation, he thought that they were necessary to lift the level of the player of Fencing , who handicap and qualifying them to represent their country in the international championship.